(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Thomas Muir: Lad O Pairts The life and work of Sir Thomas Muir (1844-1934), Mathematician and Cape Colonial Educationist Sinenhlanhla Ndaba Portraits of Survival – Volume 1: The Holocaust Brenda Gouws CHILDREN OF HOPE: The Odyssey of the Oromo Slaves from Ethiopia to South Africa Ntombiyoxolo Mqadi MARJORIE’S JOURNEY - ON A MISSION OF HER OWN Rinelle Evans